Online dispute resolution as a mode of settling e-commerce consumer disputes / Maisarah Fatin Abdul Razak, Nurul Eezwani Mohd Kamal Syazni and Nadzirah Ya'cob - Abdul Razak, Maisarah Fatin; Mohd Kamal, Nurul Eezwani; Ya'cob, Syazni Nadzirah (2012)
This is a study on online dispute resolution as an alternative form of dispute resolution in e-commerce consumer disputes. The main objective of the study is to analyse the viability of implementing online dispute resolution to deal with consumer disputes in Malaysia. The main issue that will be focused is the applicability of online dispute resolution as an alternative to e-commerce consumer disputes other than court, Alternative Dispute Resolution and Tribunal for Consumer Claims.The issue will be addressed by firstly identifying the weaknesses of the court system and alternative dispute resolution in resolving e-commerce consumer disputes in Malaysia. The study explains when ODR comes into existence, its development and its emergence. On top of that, the study will also include a comparison between ODR practices in the United States, the European Union and China. This is to consider the use of ODR in other jurisdictions so that Malaysia can adopt the best system in applying ODR in the future. Other than that, this study will also include relevant suggestions and recommendations to consumers and the Malaysian government in applying ODR in Malaysia. As a conclusion,since Malaysia has yet to have any regulation regarding ODR for ecommerce consumer dispute,therefore, a law needs to be proposed to make clear provisions so as to provide more protection to consumers in online transactions (ecommerce).